Pembudidayaan dan Pembuatan Teh Daun Binahong untuk Mengobati Penyakit Asam Urat - Havizur Rahman; Elisma Elisma; Uce Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The community service program aims to introduce binahong plants, and its benefits to overcome gout and how to cultivate. The community will be given the skill of how to make binahong leaf tea so that utilization of binahong leaves to overcome gout become more practical, right doses so the goal of therapy for gout can be achieved. Gout is one form of arthritis that is often associated with reddish, swollen, hot and stiff joints. The prevalence of gout from the year is increasing. Men have a higher risk of gout than women. Community efforts in treating gout using chemical drugs have been shown to cause serious side effects. The use of herbal medicine can be used as an alternative therapy in dealing with this disease. The binahong plant is an empirically widely used plant to treat various illness. One of them is gout. The use of this plant in gout support therapy is essential because, from the research result, this plant has many properties with minimal toxicity. The method used in this service is by providing counselling and training. The results of evaluating the implementation of cultivation and making of binahong leaf tea for the treatment of gout, many as 29 residents of RT 02 Mendalo Indah Jambi, Luar Kota Village. The benefits of binahong as a treatment for gout as well as residents also know how to cultivate binahong for self-treatment and economic improvement container of the citizens.